Examining Repetition in User Search Behavior - Sanderson, Mark; Dumais, Susan (Proceedings of ECIR 2007, 2007)
This paper describes analyses of the repeated use of search engines. It is shown that users commonly re-issue queries, either to examine search results deeply or simply to query again, often days or weeks later. Hourly and weekly periodicities in behavior are observed for both queries and clicks. Navigational queries were found to be repeated differently from others.